REKONSTRUKSI KEPEMIMPINAN PENDIDIKAN PASCA PANDEMI: Dari Emergency Leadership Menuju Adaptive Digital Leadership - Siswadi (Universitas Nahdlatul Ulama Al Ghazali Cilacap, 2022)
This study aims to analyze the reconstruction process of educational leadership in the post-COVID-19 pandemic era, shifting from emergency leadership to adaptive digital leadership. The pandemic has forced educational systems to undergo rapid transformations, resulting in a reactive and crisis-oriented leadership model focused on stability and immediate response. However, as the crisis subsides, such leadership is no longer sufficient to address the complexity of the digital era. This research employs a qualitative approach using a library research method by analyzing relevant scholarly literature published between 2018 and 2022. The findings reveal that the reconstruction of educational leadership occurs through three main phases: the emergency phase, the recovery phase, and the transformation phase. This transformation leads to the emergence of adaptive digital leadership characterized by adaptability, integration of digital technology, collaborative leadership, and data-driven decision-making. Therefore, the reconstruction of educational leadership in the post-pandemic era is not merely technical but also paradigmatic, requiring a shift in mindset, values, and leadership practices toward a more innovative, sustainable, and future-oriented model.